2020
DOI: 10.3389/fnagi.2020.618538
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and Comprehensive Automated Ventricle Segmentation on Ventricle Images of the Elderly Patients: A Retrospective Study

Abstract: Background and Objective: Ventricle volume is closely related to hydrocephalus, brain atrophy, Alzheimer's, Parkinson's syndrome, and other diseases. To accurately measure the volume of the ventricles for elderly patients, we use deep learning to establish a systematic and comprehensive automated ventricle segmentation framework.Methods: The study participation included 20 normal elderly people, 20 patients with cerebral atrophy, 64 patients with normal pressure hydrocephalus, and 51 patients with acquired hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Through reliable measurements of hepatic metastases, deep learning-based quantification might improve RECIST criteria performance. The application of deep learning-based algorithms for accurate and efficient organ and tumor segmentation has been widely reported, for example, myocardium segmentation [ 18 ], ventricle segmentation [ 19 ] and brain metastases segmentation [ 20 , 21 ]. Many specified algorithms have been developed for liver and liver lesions segmentation [ 14 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through reliable measurements of hepatic metastases, deep learning-based quantification might improve RECIST criteria performance. The application of deep learning-based algorithms for accurate and efficient organ and tumor segmentation has been widely reported, for example, myocardium segmentation [ 18 ], ventricle segmentation [ 19 ] and brain metastases segmentation [ 20 , 21 ]. Many specified algorithms have been developed for liver and liver lesions segmentation [ 14 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our clinical dataset included a much broader, unselected population of patients referred for MRI brain scans, with variable pathologies including brain tumors, surgical cavities, and infarcts. We found that discrimination was more challenging in this heterogeneous dataset compared with earlier studies with smaller datasets of < 100 cases in each group (4,7,8,16,17,33). Here we have leveraged a significantly larger dataset with a total of > 900 patients, including > 200 cases of hydrocephalus requiring shunting and > 600 cases with imaging evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Several automated (7,16,17,33,34) and semi-automated methods (4,5,8) have been proposed for detecting hydrocephalus. These studies focused on distinguishing between NPH and healthy controls, or distinguishing hydrocephalus from specific disorders such as Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…We propose a segmentation model that can automatically segment the CT images and MRI images regardless of the thickness. In our previous research, the feasibility of this model was verified [ 21 , 29 ].…”
Section: Methodsmentioning
confidence: 99%